Comparison of Reconstructive Plastic Surgery Rates and 30-Day Postoperative Complications Between Patients With and Without Psychiatric Diagnoses. (21st November 2020) - Spataro, Emily A; Olds, Cristen E; Kandathil, Cherian K; Most, Sam P
Abstract: Background: Psychiatric comorbidity is associated with greater 30-day postoperative complication rates in various surgical specialties, but is not well characterized for reconstructive plastic surgery. Objectives: The aim of this study was to compare reconstructive plastic surgery rates and 30-day postoperative complications between patients with and without psychiatric diagnoses. Methods: This was a retrospective cohort study comparing patients with and without psychiatric diagnoses. Data for January 1, 2007 to December 31, 2015 were collected from the IBM MarketScan Commercial and Medicare Supplemental Databases. Rates of reconstructive plastic surgery, demographic data, covariant diagnoses, and 30-day postoperative complications were collected. Differences between the 2 groups were assessed by multivariable logistic regression. Results: Among 1, 019, 128 patients (505, 715 with psychiatric diagnoses and 513, 423 without psychiatric diagnoses) assessed, reconstructive plastic surgery rates were between 4.8% and 7.0% in those with psychiatric diagnoses, compared with 1.6% in patients without psychiatric diagnoses. The greatest odds of undergoing reconstructive plastic surgery were in patients with body dysmorphic disorder (BDD) (adjusted odds ratio [aOR], 3.16; 95% confidence interval [CI], 1.76-5.67) and anxiety disorder (aOR, 3.08; 95% CI, 2.97-3.17). When assessing 1, 234, 206 patients (613, 400 with psychiatric diagnoses and 620, 806 without psychiatric diagnoses), all of whom underwent reconstructive plastic surgery, 2-fold greater odds of any 30-day postoperative complication was associated with psychiatric diagnoses (aOR, 2.01; 95% CI, 1.28-3.11), as well as greater odds of specific complications (surgical site infection, bleeding, and hospital admission). Eating disorder diagnosis was associated with the greatest odds of a complication (aOR, 4.17; 95% CI, 3.59-4.86), followed by nasal surgery (aOR, 3.65; 95% CI, 2.74-4.89), and BDD (aOR, 3.16; 95% CI, 1.76-5.67). Conclusions: Diagnosis of a psychiatric condition is associated with greater rates of reconstructive plastic surgery, and 2-fold greater odds of 30-day postoperative complications. Level of Evidence: 4: